STRUCTURAL FEATURES OF ORAL LIQUID OF COMPLEX SURVEY OF PATIENTS WITH ENHANCED EFFACEMENT TOOTH ENAMEL - Tkachenko, I.M. (World of Medicine and Biology, 2012)
This paper investigates the features of crystal formation oral fluid in patients with increased effacement of teeth from crystallographic analysis. Try five basic types of orientation of the crystals when dried oral fluid, in future, be used for adequate diagnosis and choice of preventive measures at different dental pathology.